2012
DOI: 10.1371/journal.pone.0048031
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of CD28 Gene Polymorphisms in Patients with Sporadic Breast Cancer in a Chinese Han Population in Northeast China

Abstract: BackgroundCD28 is one of a number of costimulatory molecules that play crucial roles in immune regulation and homeostasis. Accumulating evidence indicates that immune factors influence breast carcinogenesis. To clarify the relationships between polymorphisms in the CD28 gene and breast carcinogenesis, a case-control study was conducted in women from Heilongjiang Province in northeast of China.Methodology/Principal FindingsOur research subjects consisted of 565 female patients with sporadic breast cancer and 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…In our study two polymorphisms of CD28 gene were investigated: rs35593994G N A located in the promoter region in putative binding site for transcription factor (as it was shown by in silico analysis) and rs3116496T N C, which according to literature data is located near the splice acceptor site and therefore may contribute to aberrant mRNA splicing (Chen et al, 2012). Similarly to Veen et al (van Veen et al, 2003), we did not observe the association of rs3116496T N C with MS susceptibility.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In our study two polymorphisms of CD28 gene were investigated: rs35593994G N A located in the promoter region in putative binding site for transcription factor (as it was shown by in silico analysis) and rs3116496T N C, which according to literature data is located near the splice acceptor site and therefore may contribute to aberrant mRNA splicing (Chen et al, 2012). Similarly to Veen et al (van Veen et al, 2003), we did not observe the association of rs3116496T N C with MS susceptibility.…”
Section: Discussionmentioning
confidence: 68%
“…Therefore it may contribute to aberrant mRNA splicing. In consequence it could influence immune homeostasis by disturbing balance between different isoforms of CD28 protein (Chen et al, 2012). In fact, the study performed by Ledezma-Lozano et al (Ledezma-Lozano et al, 2011) revealed that in group of rheumatoid arthritis patients, TC genotype in rs3116496T N C was associated with the decreased level of soluble CD28 form in comparison to TT.…”
Section: Discussionmentioning
confidence: 99%
“…Costimulatory molecules play crucial roles in regulating T and B cell immune responses and homeostasis [15][16][17][18][19]. In particular, members of the cluster of differentiation (CD) family, including CD28, cytotoxic T-lymphocyte antigen 4, and inducible T-cell costimulator, are major costimulatory molecules [15][16][17][18][19][20]. CD28 is constitutively expressed on the majority of naïve T cells, while the others are expressed on activated T cells [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…CD28 is constitutively expressed on the majority of naïve T cells, while the others are expressed on activated T cells [21][22][23][24][25]. CD28 interacts with B7-1 and B7-2 on antigen-presenting cells (APCs) and induces T cell differentiation and proliferation [15,20,[26][27][28][29][30]. In addition, CD28 has been shown to enhance glucose uptake, glycolysis, production of cytokines such as interleukin-2, and cell survival through induction of the antiapoptotic factor Bcl-XL [31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation